Rehabilited winter birds of Chimdi lake (Birju Tal) Sunsari, Nepal - Jha, K.; Subba, B. R. (Nepalese Journal of Biosciences, 2015)
Chimdi lake (101.6 hect.) situated in Sunsari district is at its rehabilitating phase. Besides wetland birds several grass land, open land and garden birds also take shelter here. In the present survey altogether 60 species of bird were recorded in three months (October, November, December). Few birds like Common Shelduck, Purple Moorhen, Coot, Mallard, Eurasian Wigeon were seen to have rehabilitated whereas several species of bird such Pheasant-tailed Jacana, Ruddy Shelduck, Darter, Glossy Ibis, White Ibis, Opened Billed stork, White Necked stork, Sparrow Hawk, Dark Kite, Marsh Harrier, Golden Plover, Pheasant Tailed Jacana, Curlew, Little Egret which were recorded in the initial stage of the lake did not turn out this time. Except the population of Lesser Whistling Teal, the population other species of bird was not found increased well in spite of safe habitat and food availability.